Expression and clinical significance of extracellular matrix protein 1 and vascular endothelial growth factor-C in lymphatic metastasis of human breast cancer - Wu Qiu-Wan (BMC Cancer, 2012)
Abstract Background Extracellular matrix protein 1 (ECM1) and vascular endothelial growth factor-C (VEGF-C) are secretory glycoproteins that are associated with lymphangiogenesis; these proteins could, therefore, play important roles in the lymphatic dissemination of tumors. However, very little is known about their potential roles in lymphangiogenesis. The aim of this study was to investigate whether correlations exist between ECM1 and VEGF-C in human breast cancer, lymphangiogenesis, and the clinicopathological characteristics of the disease. Methods ECM1 and VEGF-C mRNA and protein expression levels in 41 patients were investigated using real-time reverse transcriptase polymerase chain reaction (RT-PCR), or immunohistochemical (IHC) staining of breast cancer tissue, matched noncancerous breast epithelial tissues, and suspicious metastatic axillary lymph nodes. D2-40 labelled lymph vessels and lymphatic microvessel density (LMVD) were counted. Correlations between ECM1 or VEGF-C protein expression levels, LMVD, and clinicopathological parameters were statistically tested. Results The rate of ECM1 positive staining in breast cancer tissues was higher (31/41, 75.6%) than that in the corresponding epithelial tissues (4/41, 9.8%, P < 0.001) and lymph nodes (13/41, 31.7%, P < 0.001). Similarly, the VEGF-C expression rate in cancer specimens was higher (33/41, 80.5%) than in epithelial tissues (19/41, 46.3%, P < 0.01) or lymph nodes (15/41, 36.6%, P < 0.01). Higher ECM1 and VEGF-C mRNA expression levels were also detected in the tumor tissues, compared to the non-cancerous tissue types or lymph nodes (P < 0.05). ECM1 protein expression was positively correlated with the estrogen receptor status (P < 0.05) and LMVD (P < 0.05). LMVD in the ECM1- and VEGF-C-positive tumor specimens was higher than that in the tissue types with negative staining (P < 0.05). Conclusions Both ECM1 and VEGF-C were overexpressed in breast cancer tissue samples. ECM1 expression was positively correlated with estrogen responsiveness and the metastatic properties of breast cancer. We conclude, therefore, that ECM1 and VEGF-C may have a synergistic effect on lymphangiogenesis to facilitate lymphatic metastasis of breast cancer.